Understanding air–water mass transfer in rectangular dropshafts. Issue 5 (1st September 2004) - Chanson, H.
Abstract : A dropshaft is a vertical structure connecting two channels with different invert elevations. Four configurations of rectangular dropshafts were investigated systematically to study the effects of outflow direction and pool depth on particle residence times and flow aeration. The best hydraulic design was that with 180° outflow direction and deep pool shaft. For that design, a full-scale study was conducted, the scaling ratio between prototype and model being 3.1:1. Although similar trends were seen in both model and prototype, scale effects were observed in terms of particle residence times and bubble swarm depths. In the prototype, detailed air-water flow measurements were performed in the shaft pool and the mass transfer equation was integrated using measured interfacial areas and particle residence times. The results demonstrate that the air-water mass transfer is the largest at low flow rates (regime R1) because of large residence times and significant interfacial area. Overall the present study provides new understanding of the basic mechanisms of air-water mass transfer in rectangular dropshafts.